Profitability of MV Boro Rice Production Under Shallow Tubewell Irrigation System in Some Selected Areas of Tangail District (Progressive Agriculture, 2013)
The present study estimates profitability of MV Boro rice production under shallow tubewell irrigation system. The study was conducted in Ghatail upazila of Tangail district. In the study, 60 water buyers from 5 villages were randomly selected. The survey covered a whole period of MV Boro production (January to May 2008). The major findings of the study were that about one third of total cost shared by irrigation charge. Though, the water buyers made a significant profit from MV Boro paddy production but the buyers were not fully satisfied with the prevailing one-fourth water charge and claimed for reduction of water charge. Education and farming experience was the important tools to increase profit in MV Boro paddy production. A considerable further scope apparently exists for expansion of STWs by reducing water charge to enhance the productivity of MV Boro paddy and to increase farm income of water buyers.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16877 Progress. Agric. 20(1 & 2): 237 244, 2009